KONSEP DASAR DAN KARAKTERISTIK KEPEMIMPINAN KEPALA MADRASAH ALIYAH NURUL UMMAH KOTAGEDE YOGYAKRTA - Ahmad Nur Kholik (AS-SALAM, 2020)
This article aimsto examine the basic concepts and characteristics of Madrasah principals in private schools in Yogyakarta. The Data in this research was obtained from observation, interviews, and documentation. Research resultshows that the basic concept of leadership consists of functions, traits, tasks, and the theory of the emergence of leadership and leadership characteristics. Not everyone has a leadership spirit (in the world of education), this is often found in educational institutions in Indonesia. Some theories say that leadership is hereditary, others say that leadership must go through experience and teaching first. This shows that the criteria for leadership are not based on intelligence and intelligence, but rather on the individual factors themselves. The contribution of this research to education in Indonesia is to give a new color to become an ideal leader.